D-thyroxine reduces lipoprotein(a) serum concentration in dialysis patients. - Bommer, Christiane Friederike; Werle, Egon; Walter-Sack, Ingeborg; Keller, Christine K.; Gehlen, Frank; Wanner, C.; Nauck, M.; März, W.; Wieland, H.; Bommer, Jürgen (Journal of the American Society of Nephrology, 1998)
Uremia raises lipoprotein(a) (Lp(a)) serum concentration and the risk of arteriosclerosis in dialysis patients. The treatment of high Lp(a) levels is not satisfactory today. The decrease of Lp(a) in hypothyroid patients on L-T4 therapy raised the question of whether dextro-thyroxine (D-thyroxine) reduces not only serum cholesterol, but also Lp(a) serum concentration. In a single-blind placebo-controlled study, the influence of D-thyroxine therapy on Lp(a) serum concentration was evaluated in 30 hemodialysis patients with elevated Lp(a) serum levels. Lp(a) was quantified in parallel by two methods, i.e., rocket immunoelectrophoresis and nephelometry, and apo(a) isoforms were determined by a sensitive immunoblotting technique. Regardless of the apo(a) isoforms, 6 mg/d D-thyroxine reduced elevated Lp(a) levels significantly by 27 +/- 13% in 20 dialysis patients (P < 0.001) compared with 10 control subjects (-9.9 +/- 8.4%). In parallel, D-thyroxine therapy significantly lowered total cholesterol (P < 0.001), LDL cholesterol (P < 0.001), and LDL cholesterol/HDL cholesterol ratio (P < 0.01); raised T4 and T3 serum levels; and suppressed thyroid-stimulating hormone secretion without causing clinical symptoms of hyperthyroidism in any of the patients. D-Thyroxine reduces elevated serum Lp(a) concentration in dialysis patients. The effect in nondialysis patients can be expected but remains to be proven.
Gesehen am 08.05.2024